Composition, nutritional value, and uses of Ricinodendron heudelotii, Vitex doniana, and Cleome gynandra seed oil, three indigenous oil species sources of omega 3, 6, and 9 fatty acids: A review - Honfo, Gbenato Fernande (My University, 2022)
Ricinodendron heudelotii, Vitex doniana, and Cleome gynandra are three indigenous species of Benin/West Africa. This review focuses on the physicochemical characteristics of their seeds and the nutritional and functional properties of their oils. In this systematic review, scientific articles and reports were used to collect information. The minima, maxima, and mean values were considered and converted into a dry basis and/or the same units by using the international system of units when needed to allow comparison. Seeds of Ricinodendron, Vitex and Cleome fat contents were 51.83 g/100 g dw, 28.55 g/100 g dw and 27.35 g/100 g dw, respectively. The three seed oils contained 58.54% to 87% mono and polyunsaturated fatty acids. Ricinodendron seed oil contained a conjugated polyunsaturated fatty acid α-eleostearic acid (49.3%–51.1%). Data varied from one author to another due to themethods used. R. heudelotii seeds oil is traditionally used for the treatment of several diseases. Its oil showed phytochemical and antimicrobial properties suggesting its possible use in pharmaceutical industries. Ricinodendron and Vitex seed oil should not be used for cooking at high temperatures or frying because of their high and medium levels of unsaturation.
Keywords: essential fatty acids; fat content; food applications; pharmaceutical applications; wild oil